2011
DOI: 10.1292/jvms.11-0097
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Observation of Canine Degenerative Myelopathy in Two Pembroke Welsh Corgi Dogs

Abstract: ABSTRACT. Immunohistochemistry was performed to assess whether oxidative stress and/or denatured proteins play roles in the pathogenesis of canine degenerative myelopathy (DM). Two Pembroke Welsh Corgi (PWC) dogs with a homozygous mutation (c.118G>A) in the canine superoxide dismutase 1 (SOD1) gene were examined. The pathological features of the dogs were consistent with those of previous cases of DM in PWC. In the spinal lesions, diffuse SOD1 expression was observed in the neurons while no inclusion-like aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…This confirms our earlier histopathologic demonstration of cytoplasmic SOD1 aggregate accumulation in the motor neurons from the spinal cords of DM-affected dogs 4,11. Ogawa et al16 have independently shown similarly appearing SOD1 aggregates in spinal cords from Pembroke Welsh Corgis with DM. As shown in Table3, cytoplasmic aggregates containing SOD1 antigen were found in spinal cord neurons in all but 1 of the examined dogs with histopathologically confirmed DM.…”
Section: Discussionsupporting
confidence: 90%
“…This confirms our earlier histopathologic demonstration of cytoplasmic SOD1 aggregate accumulation in the motor neurons from the spinal cords of DM-affected dogs 4,11. Ogawa et al16 have independently shown similarly appearing SOD1 aggregates in spinal cords from Pembroke Welsh Corgis with DM. As shown in Table3, cytoplasmic aggregates containing SOD1 antigen were found in spinal cord neurons in all but 1 of the examined dogs with histopathologically confirmed DM.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings, in conjunction with those of Ogawa et al () and Zhou et al () indicate that, for the intercostal muscles, muscle atrophy and sensory neuron degeneration precede the degeneration of the associated MNs. Whether this is the case for other motor units in DM remains to be determined.…”
Section: Discussionsupporting
confidence: 90%
“…These functions of astrocytes are known to be impaired in ALS (Howland et al, 2002;Clement et al, 2003;Yamanaka et al, 2008). The expression of inducible nitric oxide synthase in SOD1-positive astrocytes was previously reported in DM (Ogawa et al, 2011). The loss of glutamate transporter 1 was more recently demonstrated in the astrocytes of DM cases (Ogawa et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…It currently remains unknown whether the accumulation of insoluble proteins represents the final step in degenerated neurons or the progression of pathological changes. Awano et al reported the presence of SOD1 aggregates in the spinal neurons of dogs with DM (Awano et al, 2009); however, this finding was not confirmed in a later study (Ogawa et al, 2011). The discrepancy may stem from the specificity of the antibody used.…”
Section: Discussionmentioning
confidence: 86%